Characteristics of Phosphate, Nitrate and Dissolved Oxygen in Gangga and Siladen Island Waters, North Sulawesi - Simon I. Patty (Sam Ratulangi University, 2014)
Waters of Gangga and Siladen island, North Sulawesi is very important due to their terrestrial-influencedÂ oceanographic conditions of the Celebes Sea and the Indian Ocean that is rich in marine resources.Â Research on the characteristics of the water mass in relation with nutrients, phosphate, nitrate and dissolved oxygen were carried out in the waters Gangga island (May 2011) and Siladen island (July 2011). Phosphate and nitrate levels were analyzed using spectrophotometric method using Nicolet Evolution 100 spectrophotometer, while dissolved oxygen was determined by electrochemical methods. Statistical analysis showed that the nitrate levels in the waters of the Gangga island to the Siladen island is significantly different, while the phosphate and dissolved oxygen levels were not significantly different. The fluctuative concentration of phosphate, nitrate and dissolved oxygen in the GanggaÂ and SiladenÂ island waters were influenced by current, the mmovement of water mass, plankton activity and input from the surrounding mainland. Keywords: Phosphate, nitrate, dissolved oxygen, gangga, siladen, north sulawesi. ABSTRAK Perairan pulau Gangga dan pulau Siladen, Sulawesi Utara merupakan perairan yang sangat penting karena kondisi oseanografinya di pengaruhi daratan, Laut Sulawesi dan Samudera Hindia sehingga kaya akan sumber daya laut. Penelitian tentang karakteristik massa air kaitannya dengan zat hara fosfat, nitrat dan oksigen terlarut telah dilakukan di perairan pulau Gangga (Mei 2011) dan pulau Siladen (Juli 2011). Kadar fosfat dan nitrat dianalisa dengan menggunakan metode spektrofotometri dengan menggunakan alat spektrofotometer Nicolet Evolution 100, sedangkan oksigen terlarut ditentukan dengan metoda elektrokimia. Hasil analisis statistik menunjukkan bahwa kadar nitrat di perairan pulau Gangga dengan pulau Siladen adalah berbeda sangat nyata, sedangkan kadar fosfat dan oksigen terlarut tidak berbeda nyata. Tinggi rendahnya kosentrasi fosfat, nitrat dan oksigen terlarut di perairan pulau Gangga dan pulau Siladen dipengaruhi oleh arus, pergerakan massa air, aktiï¬tas plankton dan masukan dari daratan. Â Kata kunci: Fosfat, nitrat, oksigen terlarut, Gangga, Siladen, Sulawesi Utara.